Flow Diversion for Ruptured Tiny Internal Carotid Artery Aneurysm in Patient Allergic to Acetylsalicylic Acid: Case Report and Literature Review - Vladimir, Kalousek; David, Ozretić; Josko, Bilandzic; Kresimir, Rotim; Branimir, Culo (Journal of Neurological Surgery Reports, 2025)
Female patient, age 50, allergic to acetylsalicylic acid (ASA) presented to the emergency department of our institution with spontaneous and severe headache.Emergent brain MSCT and CTA scan showed subarachnoid hemorrhage with aneurysm in the C7 segment of left internal carotid artery (ICA). Prasugrel monotherapy was started and she underwent endovascular aneurysm occlusio. Small, atypically shaped aneurysm was found at the origin of anterior choroidal artery (AChA). Flow diverter stent was placed in the left C7 segment. One single coil was deployed in the sac. She was discharged without any neurological sequelae with prasugrel monotherapy. Two years after the procedure, aneurysm was completely occluded with normal flow in left ICA and its branches.Here, we describe case of blood-blister like aneurysm (BBA) at the origin of left AChA. There is still no consesus regarding optimal treatment strategy for BBAs. Our experience shows it is possible to treat BBA with flow diversion even in the acute setting and near origins of ICA branches. Flow diversion needs to be reinforced with aneurysm coiling in the case of ruptured aneurysm. Due to patient's ASA allergy, we opted for prasugrel monotherapy which proved to be both safe and effective antiplatelet therapy after flow diverter placement.To the best of our knowledge this is first published case in which coiling with flow diversion was used to treat BBA at the branching point of supraclinoid ICA in a patient allergic to ASA.
Keywords: blood-blister aneurysm; flow diverter; antiplatelet monotherapy; subarachnoid hemorrhage